PENGARUH ORIENTASI PASAR, ORIENTASI TEKNOLOGI DAN INOVASI PRODUK TERHADAP KEUNGGULAN BERSAING USAHA SONGKET SKALA KECIL DI KOTA PALEMBANG - Heri Setiawan (Politeknik Negeri Sriwijaya, 2012)
This research aims to analyze effect of market orientation, technology orientation and product innovation on Competitive Advantage of Songket industry specially Small Enterprises in Palembang City. This study uses data collected by a survey on Small Enterprises of Songket Company using simple random sampling method. The sample of this research consist of 91 Small Enterprises of Songket. The data analysis using SPSS software with Linear Regression Analysis. Independent variables in this research are market orientation, technology orientation and product innovation, and dependent variable is Competitive Advantage. The result shows that simultaneously market orientation, technology orientation and product innovation have significant influence on Competitive Advantage. The result shows that partially market orientation have significant influence on Competitive Advantage. Technology orientation did not have significant influence on Competitive Advantage. Product innovation has significant influence on Competitive Advantage.